Data from: Old-growth forests buffer climate-sensitive bird populations from warming - Betts, Matthew G.; Phalan, Ben; Frey, Sarah J. K.; Rousseau, Josée S.; Yang, Zhiqiang (Dryad, 2018)
Aim: Habitat loss and climate change constitute two of the greatest
threats to biodiversity worldwide, and theory predicts that these factors
may act synergistically to affect population trajectories. Recent evidence
indicates that structurally complex old-growth forest can be cooler than
other forest types during spring and summer months, thereby offering
potential to buffer populations from negative effects of warming. Old
growth may also have higher food and nest-site availability for certain
species, which could have disproportionate fitness benefits as species
approach their thermal limits. Location: Pacific Northwestern United
States. Methods: We predicted that negative effects of climate change on
30-year population trends of old-growth-associated birds should be
dampened in landscapes with high proportions of old-growth forest. We
modelled population trends from Breeding Bird Survey data for 13 species
as a function of temperature change and proportion old-growth forest.
Results: We found a significant negative effect of summer warming on only
two species. However, in both of these species, this relationship between
warming and population decline was not only reduced but reversed, in
old-growth-dominated landscapes. Across all 13 species, evidence for a
buffering effect of old-growth forest increased with the degree to which
species were negatively influenced by summer warming. Main conclusions:
These findings suggest that old-growth forests may buffer the negative
effects of climate change for those species that are most sensitive to
temperature increases. Our study highlights a mechanism whereby management
strategies to curb degradation and loss of old-growth forests—in addition
to protecting habitat—could enhance biodiversity persistence in the face
of climate warming.
Breeding Bird Survey trendsFile containing the Breeding Bird Survey trends
analysis results published by the Patuxent Wildlife Research Center on the
following website: www.mbr-pwrc.usgs.gov/bbs/. Each trends is associated
with a species' abundance and monitoring
route.BBS_birdtrends.csvEnvironmental variablesEnvironmental predictor
variables used in analysis describing location, forest cover, and
topography of BBS routes.predictors.csvR code for analysisThis file
contains annotated R code for the main analyses in the manuscript. These
are 1) Determining which month for temperature change is the best
predictor for each species' trend (June or July), 2) Trend ~
Temperature change * old-growth forest models for each species, 3) Global
trend models for Wilson's warbler and hermit warbler that include
additional interaction terms, & 4) Calculation of % change in
trend per increase in June/July temperature for Wilson's warbler and
hermit warbler.Betts_et_al_D&D_analysis_code.R
Keywords: habitat loss; synergistic effects; old-growth forest; bird populations